Advances in microbial physiology : edited by Robert K. Poole - Poole, Robert K. (Advances in microbial physiology, 2012)
Advances in Microbial Physiology is one of the most successful and prestigious series from Academic Press, an imprint of Elsevier. It publishes topical and important reviews, interpreting physiology to include all material that contributes to our understanding of how microorganisms and their component parts work. First published in 1967, it is now in its 61st volume. The Editors have always striven to interpret microbial physiology in the broadest context and have never restricted the contents to "traditional views of whole cell physiology. Now edited by Professor Robert Poole, University of Sheffield, Advances in Microbial Physiology continues to be an influential and very well reviewed series. Key features: * Contributions from leading authorities * Informs and updates on all the latest developments in the field.